2006
DOI: 10.1111/j.1530-0277.2006.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 gp120 as Well as Alcohol Affect Blood–Brain Barrier Permeability and Stress Fiber Formation: Involvement of Reactive Oxygen Species

Abstract: These results indicate that both HIV-1 gp120 and alcohol induce stress fibers, causing increased permeability of the human BBB endothelium. Alcohol (68 mM)-mediated permeability increase was linked to ROS formation. The alcohol-mediated physiological changes in the HBMEC monolayers may increase diffusion of plasma components and viral penetration across the BBB. This suggests that alcohol, especially at levels attained in heavy drinkers, can potentially contribute in a negative fashion to HIV-1 neuropathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 99%
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 99%
“…It decreases the expression of various TJPs, including occludin, ZO-1,and ZO-2,and increases the migration of monocytes into the CNS[134,135]. Gp 120 induces the production of reactive oxygen species (ROS) through NADPH to upregulate the expression of MMP2 and MMP9 in endothelial cells [136, 137]. Gp120 also interacts with neurons to decrease mitochondrial movement, resulting in mitochondrial dysfunction [125, 138].…”
Section: Role Of Hiv-1 Proteins In Neurotoxicitymentioning
confidence: 99%
“…Neurons and astroglial cells are sensitive to alcohol consumption, which promotes an apoptotic pathway of neurodegeneration. Endothelial cell apoptosis allows considering a possibility of the blood-brain barrier disfunction [18]. Despite the fact that the alcohol-induced oligodendroglial cell death has been reported previously [1], we were unable to confirm oligodendroglial damage underlying alcohol consumption.…”
Section: Discussionmentioning
confidence: 59%